Blind Face Restoration via Multi-Prior Collaboration and Adaptive Feature Fusion - Teng, Zi; Yu, Xiaosheng; Wu, Chengdong (Frontiers in Neurorobotics, 2022)
Blind face restoration (BFR) from severely degraded face images is important in face image processing, and has attracted increasing attention due to its wide applications. However, due to the complex unknown degradations in real-world scenarios, existing priors-based methods tend to restore faces with unstable quality. In this paper, we propose a multi-prior collaboration network (MPCNet) to seamlessly integrate the advantages of generative priors and face-specific geometry priors. Specifically, we pretrain a high-quality (HQ) face synthesis generative adversarial network (GAN) and a parsing mask prediction network, and then embed them into a U-shaped deep neural network (DNN) as decoder priors to guide face restoration, during which the generative priors can provide adequate details and the parsing map priors provide geometry and semantic information. Furthermore, we design adaptive priors feature fusion (APFF) blocks to incorporate the prior features from pretrained face synthesis GAN and face parsing network in an adaptive and progressive manner, making our MPCNet exhibits good generalization in real-world application. Experiments demonstrate the superiority of our MPCNet in comparison to state-of-the-arts, and also show its potential in handling real-world low-quality images from several practical applications.